Penegakan Hukum Terhadap Pelanggaran Tarif Parkir Menurut Peraturan Daerah Kota Surabaya Nomor 8 Tahun 2012 - Sanjaya, Yanuar Tri Ratna (Peneliti.net, 2024)
The Surabaya City Government issued Surabaya City Regional Regulation Number 8 of 2012 concerning Retribution for Parking Services on the Side of Public Roads to provide legal protection for vehicle users. However, in practice there are still parking officers who collect parking fees that do not comply with the set rates. In fact, parking administration and parking fees are regulated in Article 1 of Law Number 22 of 2009. This research aims to determine and analyze parking fee violations in Surabaya City Regional Regulation Number 8 of 2012 and law enforcement regarding parking fee violations. The research method uses normative juridical. The approach methods used are the statutory approach, the case approach and the conceptual approach. The data processing technique is carried out by examining and reviewing legal materials and categorizing them according to the problem formulation, then analyzing the legal materials using qualitative juridical analysis. The results of the research show that the rules regarding violations of parking fees are in Surabaya City Regional Regulation Number 8 of 2012 which regulates the structure and amount of parking fees on the side of public roads. The structure and amount of parking fees on the side of public roads as well as law enforcement against violations of parking fees based on Surabaya City Regional Regulation Number 8 of 2012 concerning Retributions for Parking Services on the Side of Public Roads.